Anxiety Modulates the Degree of Attentive Resources Required to Process Emotional Faces - Fox, Elaine (2005)
The present study contributes to the ongoing debate over the extent to which attentive resources are required for emotion perception. Although fearful facial expressions are strong competitors for attention, we predict that the magnitude of this effect may be modulated by anxiety. To test this hypothesis, healthy volunteers who varied in their self-reported levels of trait and state anxiety underwent an attentional blink task. Both fearful and happy facial expressions were subject to a strong attentional blink effect for low-anxious individuals. For those reporting high anxiety, a blink occurred for both fearful and happy facial expressions, but the magnitude of the attentional blink was significantly reduced for the fearful expressions. This supports the proposals that emotion perception is not fully automatic and that anxiety is related to a reduced ability to inhibit the processing of threat-related stimuli. Thus, individual differences in self-reported anxiety are an important determinant of the attentional control of emotional processing.